2016
DOI: 10.1108/lm-03-2016-0017
|View full text |Cite
|
Sign up to set email alerts
|

Current and required competencies of university librarians in Pakistan

Abstract: Purpose The purpose of this paper is twofold: to find out the perception of university librarians about the current and required competencies and to identify the current rank and to point out the benchmark for competencies of library professionals at public universities in Pakistan. Design/methodology/approach Quantitative research design is used for the conduct of the current study. A structured questionnaire was used to collect data. The Special Libraries Association instrument “Competencies for Informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 37 publications
2
29
0
Order By: Relevance
“…The report explains, in depth, all steps involved in the life cycle of electronic resources some of them being technical knowledge, communication skills, analytical mind and personal skills (www.nasig.org). Such kind of guidelines is needed, especially in the context of Indian scenario (Sreekumar, 2012;Khan and Bhatti, 2017;Farooq et al, 2016).…”
Section: Review Of Literaturementioning
confidence: 99%
“…The report explains, in depth, all steps involved in the life cycle of electronic resources some of them being technical knowledge, communication skills, analytical mind and personal skills (www.nasig.org). Such kind of guidelines is needed, especially in the context of Indian scenario (Sreekumar, 2012;Khan and Bhatti, 2017;Farooq et al, 2016).…”
Section: Review Of Literaturementioning
confidence: 99%
“…A later study at the same university (Anwar and Warraich, 2013) revealed that entry-level librarians were interested in expanding their "digital literacy" by undertaking a range of options through continuing professional development. Farooq et al (2016) have recently discussed the competencies required of university librarians in Pakistan in general; however, IL is not discussed specifically in any detail. Ahmed and Rehman (2016) have reported on information and communication technology (ICT) competencies among public sector university librarians in Khyber Pakhtunkhwa (heavy focus on IT).…”
Section: Information Literacy In the Pakistani Contextmentioning
confidence: 99%
“…Marketing of electronic resources. These four functions require high-level skilled trainers with diverse capabilities (Farooq et al, 2016). Libraries arrange technical and vocational training for professionals and students on the cataloging of electronic resources, database management, and web designing.…”
Section: Introductionmentioning
confidence: 99%